THE ROLE OF AI AND IOT IN STREAMLINING COMMUNICATION BETWEEN FAMILY PHYSICIANS AND PATIENTS (Journal of Medical & Health Sciences Review, 2025)
Background: AI and IoT can enhance interaction between family physicians and patients; this can be reached by integrating both Artificial Intelligence and the Internet of Things in healthcare. However, the level to which these technologies have enhanced the communication process is still a matter of some debate.Objective: This research proposes to ascertain the applicability of AI and IoT for F2G communication, engagement, and interaction by ascertaining their usage, performance in communication efficiency and effectiveness, satisfaction among patients, and effect on patient care.Methods: To achieve this research goal, the authors used quantitative, cross-sectional survey questionnaires completed by 250 respondents – both patients and FPs – who had previously interacted with AI and IoT in the context of healthcare communication. Questionnaires were self-completed online, and the analysis incorporated the Shapiro-Wilk test, Cronbach’s Alpha, and regression analysis to test normality, reliability, and AI and IoT on communication impact.Results: Therefore, the outcomes revealed that the integration of AI and IoT in healthcare communication remains relatively limited; overall, 32 % use AI tools once a month, and 23 % use them 2 times per month. It was observed that data were not normally distributed by using the Shapiro-Wilk test. Cronbach’s Alpha was 0.04, therefore the reliability of the AI and IoT questions was low, and regression analysis showed that variation in communication effectiveness could only be explained by AI and IoT usage to the extent of 1%. However, IoT tools gave patients a fairly good level of control regarding their health.Conclusion: The use of AI and IoT consequently presents benefits in improving the communication between family physicians and patients, as is the case now though not to the greatest extent. Therefore, to fully optimize its usage, there is a need for enhancement of usability, accessibility as well as reliability, and enhanced user support. Still, there are opportunities for both AI and IoT to enhance patient control and healthcare results.